1989
DOI: 10.1080/03036758.1989.10421842
|View full text |Cite
|
Sign up to set email alerts
|

Gravity interpretation profile across Hikurangi subduction zone using seismic constraints — Hawke's Bay to Hikurangi Trench

Abstract: Constraints are placed on crustal structure between Hawke's Bay and the Hikurangi Trench, Hikurangi subduction zone using seismic, microseismic and gravity data. Seismic refraction and exploration well data indicate a thickness of 5.5 kilometres for sediments beneath Hawke's Bay overlying the large negative gravity anomaly in that region, these sediments contributing about -550 p.N/kg to that anomaly. Modelling carried out using these data and new microseismic information on the geometry of the subducted Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Marine track line data are available from the U.S. National Geophysical Data Center (http://www.ngdc.noaa.gov/mgg/geodas/trackline.html). A map of the combined onshore Bouguer anomaly and offshore free‐air anomaly data (Figure 6a) is dominated by a large NE‐SW minimum, related to the Pacific Plate subducting beneath the North Island [ Bannister , 1989; Stern et al , 1993], and positive anomalies in the north and west that relate to lithospheric structure [ Stern et al , 1987] and the lack of subsidence following deposition of recently deposited sediments offshore in the Taranaki Basin [ Holt and Stern , 1991]. In the vicinity of the Taranaki Fault, these regional long‐wavelength effects (>50 km) tend to mask the shorter wavelength anomalies associated with upper crustal structure, and have been separated by computation of regional and residual gravity fields (Figures 6b and 6c) to reveal the Taranaki Fault.…”
Section: Data Sources and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Marine track line data are available from the U.S. National Geophysical Data Center (http://www.ngdc.noaa.gov/mgg/geodas/trackline.html). A map of the combined onshore Bouguer anomaly and offshore free‐air anomaly data (Figure 6a) is dominated by a large NE‐SW minimum, related to the Pacific Plate subducting beneath the North Island [ Bannister , 1989; Stern et al , 1993], and positive anomalies in the north and west that relate to lithospheric structure [ Stern et al , 1987] and the lack of subsidence following deposition of recently deposited sediments offshore in the Taranaki Basin [ Holt and Stern , 1991]. In the vicinity of the Taranaki Fault, these regional long‐wavelength effects (>50 km) tend to mask the shorter wavelength anomalies associated with upper crustal structure, and have been separated by computation of regional and residual gravity fields (Figures 6b and 6c) to reveal the Taranaki Fault.…”
Section: Data Sources and Analysesmentioning
confidence: 99%
“…Earthquake hypocenters, relocated as part of the 3‐D tomographic inversion [ Reyners et al , 2006], which occur within 30 km of the lines, are shown on the models and correlate with the position of the subducting Pacific Plate beneath the North Island. Models are constructed in a similar manner to Bannister [1989] and Holt and Stern [1994], incorporating both the overriding and subducted plate structure beneath the North Island.…”
Section: Data Sources and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 13a shows an interpretation model where the structure is taken directly from the seismic and density constraints discussed above; no load associated with the thrust belt is included. In Figure 13b Bannister 1986;1989].…”
Section: Despite the Scatter Four Important Features In The Gravity mentioning
confidence: 99%